PELATIHAN PENYUSUNAN LAPORAN PERUBAHAN EKUITAS DAN LAPORAN POSISI KEUANGAN BAGI SISWA PANTI ASUHAN ASIH LESTARI - Dermawan, Elizabeth Sugiarto; Suntono, Angelina; Edbert, Richard (Lembaga Penelitian dan Pengabdian Kepada Masyarakat Universitas Tarumanagara, 2025)
Statement of Changes in Equity and Statement of Financial Position are topics required by students at the Asih Lestari orphanage, so this PKM was carried out based on invitation no.003/YPA.AL/SK/I/2025 from the management of the Asih Lestari (AL) Orphanage. Providing an understanding of the preparation of Statement of Changes in Equity and Statement of Financial Position needs to be provided considering that students at this orphanage will live independently after high school. The topics discussed in this PKM are related to the preparation of Statement of Changes in Equity for sole proprietorships, firms, and Corporations. In addition, training was also provided on the preparation of Statement of Ffinancial Position for sole proprietorships, firms, and Corporations because they have different capital compositions. This PKM is expected to be useful in preparing students at the Asih Lestari orphanage after graduating from high school to start independent businesses, as well as to support learning at school. This PKM was carried out on Thursday, May 1, 2025 at 08.30-13.00, by means of tutorials, exercises, and evaluations through quizzes and questionnaires. This PKM creates mandatory outputs presented in SERINA, other outputs are posters and modules for HKI. In each session, an evaluation of students' understanding of the material presented has been carried out in the form of exercises that are actively answered by the students participating in this PKM. At the end of the session, a questionnaire was made to evaluate the implementation of this PKM via Google Form, the results of which showed that this PKM was beneficial for the students participating in this PKM. Laporan Perubahan Ekuitas dan Laporan Posisi Keuangan merupakan topik yang diperlukan oleh siswa panti asuhan Asih Lestari sehingga PKM ini dilakukan atas dasar undangan no.003/YPA.AL/SK/I/2025 dari pengelola Panti Asuhan Asih Lestari (AL). Pembekalan pemahaman tentang penyusunan laporan perubahan ekuitas dan laporan posisi keuangan perlu diberikan mengingat siswa panti asuhan ini akan hidup mandiri selepas SMA. Topik yang dibahas dalam PKM ini terkait penyusunan laporan perubahan ekuitas bagi perusahaan perorangan, firma, dan PT. Di samping itu juga diberikan pelatihan penyusunan laporan posisi keuangan bagi perusahaan perorangan, firma, dan PT karena memiliki komposisi modal yang berbeda. PKM ini diharapkan bermanfaat untuk mempersiapkan siswa panti asuhan Asih Lestari setelah lulus SMA merintis usaha mandiri, juga untuk menunjang pembelajaran di sekolah. PKM ini telah dilaksanakan pada hari Kamis tanggal 1 Mei 2025 pukul 08.30-13.00, dengan cara tutorial, latihan, dan evaluasi melalui kuis serta angket. PKM ini membuat luaran wajib yang disajikan dalam SERINA, luaran lainnya poster dan modul untuk HKI. Di setiap sesi telah dilakukan evaluasi pemahaman siswa terhadap materi yang disampaikan berupa latihan yang dijawab secara aktif oleh siswa-siswi peserta PKM ini.. Di akhir sesi dibuat angket untuk evaluasi pelaksanaan PKM ini via Google Form yang hasilnya menunjukkan PKM ini bermanfaat bagi siswa-siswi peserta PKM ini.